2016
DOI: 10.1086/688919
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Inbreeding Avoidance and Inbreeding Preference through Mate Choice among Interacting Relatives

Abstract: While extensive population genetic theory predicts conditions favoring evolution of self-fertilization versus outcrossing, there is no analogous theory that predicts conditions favoring evolution of inbreeding avoidance or inbreeding preference enacted through mate choice given obligate biparental reproduction. Multiple interacting processes complicate the dynamics of alleles underlying such inbreeding strategies, including sexual conflict, distributions of kinship, genetic drift, purging of mutation load, dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 113 publications
1
61
0
Order By: Relevance
“…This formulation ensures that the relationship between kij and the magnitude of inbreeding depression in offspring is consistent across replicate simulations. This choice, as opposed to a more mechanistic model of inbreeding depression that allows purging, is further justified because previous genetically explicit modelling (Duthie & Reid, ) showed that inbreeding avoidance in biparental populations has a negligible effect on load given small‐effect deleterious mutations (see also Wang et al ., ; Guillaume & Perrin, ).…”
Section: Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…This formulation ensures that the relationship between kij and the magnitude of inbreeding depression in offspring is consistent across replicate simulations. This choice, as opposed to a more mechanistic model of inbreeding depression that allows purging, is further justified because previous genetically explicit modelling (Duthie & Reid, ) showed that inbreeding avoidance in biparental populations has a negligible effect on load given small‐effect deleterious mutations (see also Wang et al ., ; Guillaume & Perrin, ).…”
Section: Modelmentioning
confidence: 99%
“…Offspring that are viable after the Bernoulli trial become adults. Given our current objectives, we simulate evolution under conditions where inbreeding avoidance is adaptive due to strong inbreeding depression, not where inbreeding preference is adaptive due to weak or zero inbreeding depression (Parker, ; Kokko & Ots, ; Duthie & Reid, ) or outbreeding depression (Bateson, ; Greeff et al ., ). However, as described above, positive Mp and Fp values resulting in inbreeding preference are not precluded from evolving, and could potentially arise due to mutation or drift.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations